La Biblioteca della Külliye di Kavála - vol. II - Barbara, Bruni (Scuole di dottorato, 2005)
This study represents the continuation and, to an extent, the completion of research relating to an Islamic educational and philanthropic institution, currently located in Greece. Through repeated inspections and a lengthy labour of comparison, not only have the works conserved in the institute of Kavála been catalogued, but the composition of the entire library has been almost completely reconstructed, identifying ulterior fonds belonging to the same. The research has also appraised implications functional to defining both the cultural profile of the institution and a historic phase that was of particular importance in terms of the innovations in method and content introduced into the transmission of knowledge in the Islamic world.